A Case Study of Three Swedish Hospitals’ Strategies for Implementing Lean Production - Eriksson, Andrea; Holden, Richard J.; Williamsson, Anna; Dellve, Lotta (Nordic Journal of Working Life Studies, 2016)
Many hospitals have recently implemented the management concept lean production. The aim of this study was to learn how and why three Swedish hospitals selected and developed their hospitalwide lean production strategies. Although previous research shows that the concept is implemented in various ways, there is limited research on how and why different hospitals choose different implementation strategies and if the chosen strategies contribute to sustainable participation in organizational development. A case study of three different Swedish hospitals implementing lean production was thus performed. We studied the content of the hospitals’ selected implementation strategies, conditions and rationales behind their strategy selection, and how different organizational actors participated in the implementation. Qualitative interviews with 54 key actors at the studied hospitals were performed. In addition, a self-administered survey questionnaire to employees was answered at T1 (2012, n = 557), T2 (2013, n = 554), and T3 (2014, n = 366). The three studied hospitals chose different strategies for implementing lean production due to different contextual conditions and for different reasons. The hospital-wide implementation strategies were related to employees’ interest and participation in lean production. The results show that many different actors at different organizational levels need to participate in lean production in order to sustain and diffuse change processes. Furthermore, broad motives including quality of care seem to be needed for engaging different professional groups.